2017
DOI: 10.1124/jpet.116.238212
|View full text |Cite
|
Sign up to set email alerts
|

The Glycolytic Enzyme PFKFB3 Is Involved in Estrogen-Mediated Angiogenesis via GPER1

Abstract: The endogenous estrogen 17-estradiol (E2) is a key factor in promoting endothelial healing and angiogenesis. Recently, proangiogenic signals including vascular endothelial growth factor and others have been shown to converge in endothelial cell metabolism. Because inhibition of the glycolytic enzyme activator phosphofructokinase-2/fructose-2,6-bisphosphatase 3 (PFKFB3) reduces pathologic angiogenesis and estrogen receptor (ER) signaling stimulates glucose uptake and glycolysis by inducing PFKFB3 in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 61 publications
(93 reference statements)
6
49
0
Order By: Relevance
“…Polarized activation of Cdc42, Rac1 and RhoA is required for directional cell migration 3,4 . In agreement with previous studies 14,17,4548 , our pharmacological data shows excess estrogen signaling promotes an increased activation of PI3K and Rho GTPase signaling. Importantly, it also indicates that hyperactivation of these pathways induces cell-cell disconnections within the intersegmental and axial vessels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Polarized activation of Cdc42, Rac1 and RhoA is required for directional cell migration 3,4 . In agreement with previous studies 14,17,4548 , our pharmacological data shows excess estrogen signaling promotes an increased activation of PI3K and Rho GTPase signaling. Importantly, it also indicates that hyperactivation of these pathways induces cell-cell disconnections within the intersegmental and axial vessels.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that excess estrogens predominantly signal via Esr1 and Gper1, albeit a cooperative synergism with Esr2a and Esr2b may contribute to the etiology of the vascular defects. In addition to promoting Vegfa expression, ESR1 and GPER1 signaling from the plasma membrane promotes EC migration via activation of PI3K/AKT signaling and downstream effectors in the endothelium 14,17,4548 . We show that endothelial Gper1 overexpression is sufficient to induce cell-cell disconnections and excessive migration, demonstrating for the first time a cell-autonomous role for Gper1 signaling in the etiology of vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…We previously established that E2 promotes angiogenesis via GPER-mediated rapid signaling and up-regulation of the key glycolytic protein PFKFB3 as a downstream effector. 17 Herein we showed that treatment with the selective GPER agonist G1 39 increased PFKFB3 protein levels in a time-dependent manner without affecting mRNA levels. PFKFB3 expression is tightly controlled at genomic and non-genomic levels to trigger glycolysis in a time-and spatial-specific way.…”
Section: Discussionmentioning
confidence: 77%
“…16,31 Conversely, we recently established that E2 promotes endothelial cell metabolism and angiogenesis by increasing PFKFB3 protein but not its mRNA levels in HUVECs. 17 To further investigate the mechanism of estrogen PFKFB3 regulation in HUVECs, we analyzed at different time points the effect of the selective GPER agonist G1. Similarly to what previously reported for E2, treatment with G1 (100 nM) increased PFKFB3 and the effect was maximum at 3 hours ( Figure 1A).…”
Section: G1 Increased Endothelial Pfkfb3 Levels Via Transcription-indmentioning
confidence: 99%
“…The effects of estrogens on metabolic changes in pulmonary vasculature are unknown. Nonetheless, E2, via ERα-mediated upregulation of glycolytic enzymes, not only stimulates pathologic angiogenesis in breast cancer [186], but also boosts a mitogenic response in highly proliferative human endometrial cells and umbilical vein endothelial cells [187,188]. In contrast, because 2ME is a strong HIF-1α inhibitor, 2ME would be expected to inhibit metabolic reprograming in PAH.…”
Section: Me Hif-1α and Metabolic Reprograming In Pahmentioning
confidence: 99%